Exploring the Qur’an - Lamya Sidky (International Institute of Islamic Thought, 2018)
Exploring the Qur’an: Context and Impact is a highly perceptive, technical study of the Qur’anic text that seeks to exonerate the Qur’an from claims of extremism, intolerance, or incoherence. This is accomplished through contextualizing the content and highlighting the impact of the Qur’anic message as applied throughout history. The underlying premise of its approach is that a perceptive and faithful reading of the Qur’an will result in the Qur’an exonerating itself through consistency in its own messages, rhetorical devices, and norms. In essence, it is a specific way of applying tafsīr al-Qur’ān bil-Qur’ān (explanation of the Qur’an by the Qur’an). This book is unique in the field of Qur’anic coherence in that it presents a consistent method of interpretation that is applied to a diverse range of Qur’anic subjects, not simply a study of the Qur’an’s structure nor primarily of its Arabic. It builds on previous efforts, such as Mustansir Mir’s summary of Hamid al-Din ‘Abd al-Hamid al-Farahi’s work on Qur’anic oaths, Majmū‘ati- Tafsīr-i-Farāhī, yet advances its own distinctive premise. The book has three sections, each consisting of several chapters, five of which are original to this book. This does not detract from the cohesiveness of the book. Abdel Haleem’s technical yet accessible style pervades throughout and consistency in his chosen axioms of interpretation tie the book’s parts together ...